THE RELATIONSHIP BETWEEN HYPERTENSION KNOWLEDGE WITH EATING HABITS AND BODY MASS INDEX (BMI) IN MALANG - Panjaitan, Damaris Gabrielle Valentine; Zuhriyah, Lilik; Setijowati, Nanik (Universitas Brawijaya, 2024)
Hypertension or high blood pressure is a commonly found cardiovascular disease and also the highest cause of death in society. Hypertensive patients who have good knowledge regarding their disease are known to have great treatment adherence and in their salt reduction habits. Hence, having better knowledge is expected to form healthier habits and reduce the risk of developing hypertension. This study aims to determine the relationship between hypertension knowledge, eating habits, and body mass index (BMI) in Malang. The research was conducted by distributing an online questionnaire in form of Google Forms in October 2021 and January 2022 to people who reside in Malang. This research used an observational analytic approach and cross-sectional design. Data needed in this study was taken using a demographic questionnaire, Hypertension Knowledge-level Scale that was translated to Indonesian, and modified questions from Consumptions of High-Risk Diet from the Basic Health Research 2016 conducted by the Ministry of Health of Indonesia. 212 respondents submitted the questionnaire. Based on the result, most respondents have a high knowledge level (75,9%), normal eating habits (85,8%), and abnormal body mass index (67,5%). Chi-Square test results indicated a significant relationship between knowledge and eating habits (p=0,017), no significant relationship between knowledge and body mass index (0,369), and no significant relationship between eating habits and body mass index (p=0,524).